In vitro regeneration of Majorana hortensis Moench from callus and nodal stem segments - Pai, P V Iyer, J S (Journal of Spices and Aromatic Crops, 2000)
Rapid multiplication of Majorana hortensis was achieved through plant regeneration from nodal stem explants and callus. Nod-al stem explants cultured on Murashige and Skoog’s medium supplemented with 2 mg/I benzylaminopurine and maltose as source of carbon, yielded up to 40 shoots. The shoots produced roots in the presence of 0.2 mg/l indole-3-butyric acid. Callus was induced in stem explants in medium containing 0.4 mg/12,4-dichlorophenoxy acetic acid. This callus showed organogenesis in Murashige and Skoog’s medium containing 3 mg/l benzylaminopurine and 0.2 mg/I indole-3-butyric acid.